(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article compares and analyzes the position and meaning of the noun phrase in the Azerbaijani and Kyrgyz languages. The structure of numerals in these languages, their types and functions in sentences were considered, grammatical similarities and differences were determined.